How new languages emerge - Lightfoot, David, 1945- (Cambridge University Press, 2006)
"New languages are constantly emerging, as existing languages diverge into different forms. To explain this fascinating process, we need to understand how languages change and how they emerge in children. In this pioneering study, David Lightfoot explains how languages come into being. He explores how new systems arise, how they are acquired by children, and how adults and children play different, complementary roles in language change. Lightfoot distinguishes between 'external language' (language as it exists in the world) and 'internal language' (language as represented in an individual's brain). By examining the interplay between the two, he shows how children are 'cue-based' learners, who scan their external linguistic environment for specified structures, making sense of the world outside in order to build their internal language. The internal properties of human brains provide the means to interpret speech. Engaging and original, this book offers a pathbreaking new account of language acquisition, variation, and change."--Publisher's description